Tailored Target Ablation Index Guided Pulmonary Vein Isolation in Treating Paroxysmal Atrial Fibrillation: A Single Center Randomized Study in Asian Population (AI-Asian-I) - Xiong, Qingsong; Liao, Jia; Chen, Weijie; Xiao, Peilin; Du, Huaan; He, Qushuai; Yin, Yuehui; Ling, Zhiyu; Chen, Shaojie (Frontiers in Cardiovascular Medicine, 2022)
Objective To evaluate the efficacy and safety of lower ablation indexes (AI) guided pulmonary vein isolation (PVI) in treating paroxysmal atrial fibrillation (AF). Methods Ninety patients with paroxysmal AF scheduled for radiofrequency ablation were randomly divided into three groups. The AI targets for PVI were as follows: In group A/B/C, 550/500/450 for roof and anterior wall, and 400/350/300 for posterior/inferior wall. The first-pass PVI rate, ablation time, complications and recurrence of atrial tachyarrhythmia (ATa) were compared. Results The mean age was 62.5 years (male: 63.0%), mean body mass index (BMI): 24.35 ± 3.66 kg/m2. The baseline characteristics were comparable. There was no significant difference in the first-pass PVI rate among the three groups (left-sided-PV: 66.7% vs. 80% vs. 73.3%, P = 0.51; right-sided-PV: 70% vs. 83.3% vs. 73.3%, P = 0.64), also with similar gap rate during the procedural waiting time. At 1-year follow-up there was no significant difference in the recurrence rate of ATa among the three groups (10% vs. 13.3% vs. 13.3%, P = 1.00). The ablation time in the Group C was significantly less than that in the other two groups (47.8 min. vs. 47.0 min. vs. 36.6 min, P < 0.001). Higher AI seemed to link a non-significant trend toward higher rate of pericardial effusion (group A + B vs. group C:6.7% vs. 0%, P = 0.30), although the rate of overall complications was not different among the three groups. Conclusion This randomized study shows that, a relatively lower target AI guided ablation may be similarly effective to achieve PVI with significantly reduced ablation time and obtain similar clinical outcome in treating paroxysmal AF in Asian population. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NCT:04549714].